Research on safety early warning of abnormal A-annular pressure of “three-high” gas wells based on data mining - Yan, Hongqiao; Qi, Junliang; Wu, Shuncheng; Wang, Shunyi; Zhong, B. T. (Frontiers in Earth Science, 2023)
A major safety accident will be triggered when the A-annular pressure value of high pressure, high productivity and high sulfur gas well exceeded the maximum allowable value. The A-annular pressure value of high pressure high productivity and high sulfur gas well once exceeded the allowable value will trigger a major safety accident. Therefore, this paper proposed a data mining based the gas well early warning strategy by analyzing the annular pressure mechanism and the change in the pattern of instantaneous gas volume, well temperature, and annular pressure in various conditions. To summarize, the law of gas well abnormal A-annular pressure is aimed at constructing a gas well safety warning rule for gas well stable production stage and shutdown period where the initial parameters setting in the early warning rule and adjustment optimization mechanism is also determined. Lastly, with the use of historical abnormal samples, the gas well early warning strategy bought up in this paper was verified. The example shown that compared with the traditional DCS system warning strategy, the gas well safety early warning strategy can identify the abnormal A-annular pressure phenomenon 82 h in advance thus achieving production safety management.